Implementasi Pembelajaran Content and Language Integrated Learning (CLIL) Berbasis STEM dalam Meningkatkan Speaking Skill Mahasiswa PGSD - Agustina Pali; Yuliani Sepe Wangge (Universitas Negeri Makassar, 2026)
This study aimed to improve the speaking skills of Primary School Teacher Education (PGSD) students through the implementation of STEM-based Content and Language Integrated Learning (CLIL). This research employed Classroom Action Research (CAR) conducted in two cycles involving PGSD students as the research subjects. Each cycle consisted of planning, action, observation, and reflection stages. Data were collected using student activity observation sheets and speaking skill tests. The data were analyzed using descriptive quantitative and qualitative methods. The results indicated a significant improvement in students’ speaking skills from the pre-cycle to Cycle I and Cycle II, covering aspects of fluency, pronunciation, vocabulary mastery, and self-confidence. In addition, students’ learning participation also showed improvement. Therefore, STEM-based CLIL was proven effective in enhancing the speaking skills of PGSD Flores University students and can be considered an alternative strategy for English language learning in higher education.